Predicting speech-in-noise ability in normal and impaired hearing based on auditory cognitive measures - Griffiths, Timothy D. (Frontiers in Neuroscience, 2023)
Problems with speech-in-noise (SiN) perception are extremely common in hearing loss. Clinical tests have generally been based on measurement of SiN. We develop an approach to SiN based on the auditory cognitive mechanisms that subserve this, that might be relevant to speakers of any language. We describe how well these predict SiN, the brain systems for them, and tests of auditory cognition based on them that might be used to characterise SiN deficits in the clinic.